Health care professionals' perspectives on screening and management of gestational diabetes mellitus in public hospitals of South India - a qualitative study - Biswamitra Sahu; Giridhara R. Babu; Kaveri Siddappa Gurav; Maithili Karthik; Deepa Ravi; Eunice Lobo; Daisy Abu John; Laura Oakley; Eugene Oteng-Ntim; Iliatha Papachristou Nadal; Sanjay Kinra (BMC, 2021)
Abstract Background Women developing Gestational Diabetes Mellitus (GDM) are subsequently at a higher risk of developing Type 2 Diabetes later in life. Screening and effective management of women with GDM are essential in preventing progression to type 2 diabetes mellitus. We aimed to explore the perspectives of healthcare providers regarding the barriers from the health system context that restrict the timely screening and effective management of GDM. Methods We conducted six in-depth interviews of health care providers- four with nurses and two with obstetricians in the public hospitals in India's major city (Bengaluru). The interviews were conducted in the preferred language of the participants (Kannada for nurses, English for the obstetricians) and audio-recorded. All Kannada interviews were transcribed and translated into English for analysis. The primary data were analyzed using the grounded theory approach by NVivo 12 plus. The findings are put into perspective using the socio-ecological model. Results Health care providers identified delayed visits to public hospitals and stress on household-level responsibilities as barriers at the individual level for GDM screening. Also, migration of pregnant women to their natal homes during first pregnancy is a cultural barrier in addition to health system barriers such as unmet nurse training needs, long waiting hours, uneven power dynamics, lack of follow-up, resource scarcity, and lack of supportive oversight. The barriers for GDM management included non-reporting women to follow - up visits, irregular self-monitoring of drug and blood sugar, trained staff shortage, ineffective tracking, and lack of standardized protocol. Conclusion There is a pressing need to develop and improve existing GDM Screening and Management services to tackle the growing burden of GDM in public hospitals of India.